(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
It is a qualitative research study that explores (through an autobiographical lens) a case study aimed at identifying, describing, understanding, reflecting upon, and analyzing the formative frameworks designed and implemented within the Teaching Practicum Workshop IV and Academic Forum. Curricular components of the final stage of the Practicum Pathway in the Primary Education Teacher Training Program, Plan N°528/09, at (Higher Normal School) Escuela Normal Superior N°31 “Republic of Mexico,” located in the city of San Justo, province of Santa Fe. The central objective of this research is to examine whether these teacher-training frameworks foster singular practices of kindness. Methodologically, the study adopts a kaleidoscopic perspective to portray the unique construction of a complex case, and employs the concept of “crystallization” as an analytical tool. The thesis deepens the notion of kindness in the design and implementation of formative frameworks and investigates its influence on professional teaching practices. While acknowledging the limitations inherent in a case study approach, the research also offers lines of continuity for future exploration.